THE EFFECT OF LEADERSHIP STYLE, WAGES AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. X - I Nyoman Arif Kurniawan; Artita Devi Maharani; Avivah Rahmaningtyas (Fakultas Pertanian UST, 2023)
This study aims to analyze the effect of leadership style, wages and work discipline on employee performance at PT X. The basic research method is to use quantitative research with the sampling technique using purposive proportional random sampling. The total population of 202 employees with a sample size of 135 employees consisting of permanent, apprentice and contract employees. The data analysis method used is multiple linear regression. The results of multiple linear regression analysis show a significant effect partially on the variables of wages and work discipline on employee performance at PT X, while leadership style has no partial effect on employee performance at PT X. Based on the results of the simultaneous hypothesis test (F test), it shows that simultaneously or jointly the independent variables (leadership style, wages and work discipline) have a significant effect on the dependent variable (employee performance). PT X needs to improve or evaluate the leadership style that is applied so that it can improve employee performance. Keywords: Work Discipline, Leadership Style, Employee Performance, Wages